Evaluasi Layanan Toko Berdasarkan Prinsip Ekonomi Islam: Penelitian - Nur Anggraini; Daud; Siti Fatimah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Competition in the business world is a determining factor for the success or failure of a company. Companies that are unable to follow market dynamics will be eliminated, while companies that are innovative and able to satisfy customers will win the competition and continue to grow. Customer satisfaction is the main key in creating long-term relationships between companies and consumers. Therefore, quality service is an important factor that must be maintained and improved by every business actor. This study aims to determine the quality of employee service, especially from an Islamic economic perspective, at Toko Dua Putri. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. Informants in this study include shop owners, employees, and consumers who are directly involved in service activities. The data obtained are then analyzed descriptively to understand the application of Islamic principles in service. The results of the study indicate that the services provided by Toko Dua Putri employees have reflected Islamic values ​​such as mutual assistance (ta'awun), providing convenience (at-taysir), equality (musawah), and kinship (ukhuwah).